First record of Aspergillus nomiae as a broad-spectrum entomopathogenic fungus that provides resistance against phytopathogens and insect pests by colonization of plants - Zhang, Zhengkun; Tian, Yifan; Sui, Li; Lu, Yang; Cheng, Ke; Zhao, Yu; Li, Qiyun; Shi, Wangpeng (Frontiers in Microbiology, 2024)
Introduction: Aspergillus nomiae is known as a pathogenic fungus infect humans and plants, but never has been reported as entomophagous fungus (EPF) and provided other functions as endotype.Methods: A strain of EPF was isolated and identified from diseased larvae of Spodoptera litura in a soybean field, and designated AnS1Gzl-1. Pathogenicity of the strain toward various insect pests was evaluated, especially the ability to colonize plants and induce resistance against phytopathogens and insect pests.The isolated EPF strain AnS1Gzl-1 was identified as A. nomiae, it showed strong pathogenicity toward five insect pests belonging to Lepidoptera and Hemiptera. Furthermore, the strain inhibited the growth of Sclerotinia sclerotiorum in vitro, a causual agent of soil-borne plant disease. It colonized plants as an endophyte via root irrigation with high colonization rate of 90%, thereby inducing plant resistance against phytopathogen infection, and disrupting the feeding selectivity of S. litura larvae.Discussion: This is the first record of a natural infection of A. nomiae on insects. A. nomiae was potential to be used as a dual biocontrol EPF because of its abilities to not only kill a broad-spectrum of insect pests directly, but also induce resistance against phytopathogens via plant colonization.